Physico-Chemical and Bacteriological Assessment of Bago River, Negros Occidental - Linaugo, Joji D.; Turbanos, Ferdinand M.; Pacalioga, Jessica O.; Patiluna, Ma. Lotus E.; Menes, Carmen C. (Silliman Journal, 2022)
The Bago River in Negros Occidental, Philippines was surveyed July to September 2009 (wet season) and February to April 2010 (dry season). The timing of the dry season survey coincides with the occurrence of El Niño phenomenon. Measured in-situ were depth, width and surface water velocity for hydrological and dissolved oxygen, humidity, pH, salinity and temperatures of both air and water subsurface for physico-chemical characteristics. Water samples were tested for conductivity, nitrates, phosphates, total dissolved solids, total suspended solids, and turbidity in the laboratory. Total coliform and thermo-tolerant (fecal) coliform counts were also determined. #BTFEPO%"0 UIFXBUFSPG#BHP3JWFSDBOCFDMBTTJmFEBT Class AA for dissolved oxygen, pH, phosphates and total dissolved solids; Class B for nitrates and total suspended solids; and Class D for total and fecal coliforms. Volume of water was lower during UIFESZTFBTPOUIBUCSPVHIUTPNFTJHOJmDBOUEJGGFSFODFT VTJOH t-test) in the following parameters: atmospheric temperature (p = 0.005); sub-surface temperature (p = 0.035); humidity (p = 0.000); salinity (p = 0.022); total suspended solids (p = 0.033); turbidity (p = 0.000); nitrate (p = 0.000); and phosphate (p = 0.048). The high level (2,200—16,000,000 MPN/100 ml) of coliform readings can be attributed to the observed use of the river as dumping site of human, animal and agricultural wastes. Cultivation near the upper three sampling areas and slash and burn farming in the vicinity of uppermost station might have contributed to high levels of nitrates and total suspended solids. It is recommended that local government units create and strictly implement measures regulating these activities.